Forensic analysis of mobile applications - Constantinov, Daria (2018)
The increased use of different types of applications on mobile phones makes these devices a goldmine of personal information for forensic investigators. Mobile devices can store potential evidence, which can be acquired with the forensic tools and analysis. This bachelor’s thesis focuses on performing forensic analysis of twelve mobile applications, such as Messenger, WhatsApp, Viber, iMessage, Google Chrome, Safari, Firefox, Opera Mini, Google Maps, Apple Maps, Mapy.cz, and Waze. The applications are categorized into three types of mobile applications, namely communicating, maps and navigation, and browsing. The study was conducted on iPhone 6, on which were installed mentioned applications. In each application were performed specific user activities. Then three types of extractions were conducted, specifically logical, file system, and advanced logical. After that manual forensic analysis was performed on the acquired data. The forensic analysis aimed to determine whether specific activities conducted through chosen applications were saved and stored on the device. The study led to the conclusion that almost no traces could be recovered from applications for navigation, except Waze. Applications for socializing and browsing gave the opportunity to extract a substantial amount of valuable personal data that can be used by forensic investigators for solving criminal cases.